Unfolding wasteland : a thick mapping approach to the transformation of charleroi’s industrial landscape (2019)
‘The land, so heavily charged with traces and with past readings, seems very similar to a palimpsest’ (Corboz 1985: 190). Any territory is the result of multiple and simultaneous processes; some are taking place spontaneously, others as the direct result of human interventions. (Secchi 1990; Secchi and Viganò 2009) For urbanists, a territory is a constructed physical and mental entity, where several socio-economic and cultural processes generated a juxtaposition of urban elements that at first sight seem to lack any coherence (De Meulder 2008). Nevertheless, a closer look allows an understanding into the order- ing logics that determine through time the continuous production and reproduction of space (Harvey 2001). These logics are embodied in the territory itself, making it comparable to a ‘palimpsest’, in which the traces of recent and ancient modifications ‘lie’ (Corboz 1985: 190). As Vittoria Di Palma suggests, each action on the territory, either good or bad, leaves traces and ‘we cannot wish them away’ (Di Palma 2014: 01).